STRUKTUR KEPRIBADIAN TOKOH UTAMA KANEKI KEN DALAM ANIME TOKYO GHOUL KARYA SUI ISHIDA - I Putu Adi Surya Dharma; Wayan Nurita; Ladycia Sundayra (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2023)
This thesis discusses the personality and inner conflict of the main character in the Tokyo Ghoul anime by Sui Ishida. The theory used is Sigumnd Freud's psychoanalytic personality theory and Kurt Lewin's psychoanalysis. Data collection methods and techniques used in this study are the listening method and the note-taking technique. Methods and techniques of data analysis using descriptive qualitative method. Meanwhile, the methods and techniques for presenting the results of data analysis using informal methods. The results of the analysis in this thesis, it was found that the dominant personality possessed by Kaneki's character is the aspect of the superego. Able to make Kaneki able to judge which things are good and which are bad in the midst of temptation from id. The ego has tried several times to realize the wishes of the id but the superego can always mediate between the id and the ego but over time and the many conflicts experienced by Kaneki make his personality begin to change into a cold person.